Peningkatan Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi melalui Media Infografis - Susilowati, Sulis; Anistyasari, Yeni (Jurnal Pendidikan Madrasah, 2024)
The application of infographic media in the learning of economics subjects aims to increase students' understanding of complex abstract concepts and motivate their involvement in the learning process. Infographic media is a data visualization tool that presents information in a concise, interesting, and easy-to-understand manner. This study uses an experimental approach by involving high school students as research subjects. The results of the study show that the use of infographic media significantly improves student learning outcomes, especially on topics that require an analytical understanding such as economic cycles, inflation, demand, and supply. Students report that infographics make it easier for them to understand the relationships between economic variables through a combination of images, graphs, and short text. In addition, the application of this media also increases students' active participation in class discussions, because it is easier for them to visualize the concepts taught. Thus, infographic media is not only effective in improving concept understanding, but also provides a more interactive and enjoyable learning experience. The implementation of infographic media is expected to be one of the innovations in economic learning that can be adapted for various levels of education.